2019
DOI: 10.3390/molecules24234382
|View full text |Cite
|
Sign up to set email alerts
|

Phytofabrication of Silver/Silver Chloride Nanoparticles Using Aqueous Leaf Extract of Oedera genistifolia: Characterization and Antibacterial Potential

Abstract: In this present study, silver nanoparticles (Ag/AgCl NPs) were synthesized using an aqueous leaf extract of Oedera genistifolia as a reducing agent. The biosynthesized Ag/AgCl NPs was characterized by UV-visible spectrophotometry, transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). In addition, sequel to antibacterial assay, the cytotoxic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 52 publications
13
51
0
Order By: Relevance
“…They corresponded to (111), (200), (220), (311), (222), (400), (331), and (420) planes, respectively, and confirmed the face-centered cubic (FCC) structure of AgCl according to the database of Joint Committee on Powder Diffraction Standards (JCPDS), file number 31-1238. XRD analysis confirmed that biogenic AgCl-NPs were synthesized [11]. According to the Debye-Sherrer equation, the average crystalline size of biosynthesized AgCl-NPs was 28.6 nm.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 76%
See 1 more Smart Citation
“…They corresponded to (111), (200), (220), (311), (222), (400), (331), and (420) planes, respectively, and confirmed the face-centered cubic (FCC) structure of AgCl according to the database of Joint Committee on Powder Diffraction Standards (JCPDS), file number 31-1238. XRD analysis confirmed that biogenic AgCl-NPs were synthesized [11]. According to the Debye-Sherrer equation, the average crystalline size of biosynthesized AgCl-NPs was 28.6 nm.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 76%
“…It was established that only in case of the addition of the 6% (v/v) extract to a 1 mmol/L AgNO 3 solution, would bioreduction and biosynthesis processes take place, and the colorless AgNO 3 solution became dark brown with time ( Figure 1). This is likely attributable to the completion of the synthesis process, and the formation of biogenic AgCl-NPs [11]. It was previously reported that P. vulgaris contains alkaloids, tannins, flavonoids, and phenolic compounds [29] that could be responsible for the bioreduction of Ag(I) ions into AgCl-NPs as well as their capping in the solution [30].…”
Section: Visual Confirmation Of Green Synthesis Of Agcl-npsmentioning
confidence: 98%
“…The biosynthesis of AgNPs was carried out as described by Okaiyeto et al [45] with a slight modification. Fifty millilitres (50 mL) of aqueous leaf extract of S. officinalis was added to 450 mL of 1 mM silver nitrate (AgNO 3 ) solution and the mixture was stirred in the dark at room temperature for 1 h for complete synthesis.…”
Section: Biosynthesis Of Agnpsmentioning
confidence: 99%
“…1). The colour change observed in AgNO 3 could be due to the surface plasmon resonance (SPR) excitation at 323 nm that indicates the formation of AgNPs [45,48,49]. The appearance of dark-brown colour ascribed to the surface plasmon could be as a result of the collective oscillation of free electrons of the silver nanoparticles in resonance with the frequency of the light wave interactions causing the SPR band to appear in the visible and infrared region [50,51].…”
Section: Uv-vis Spectroscopy Analysismentioning
confidence: 99%
“…The cytotoxic potential of plant extracts was evaluated against HeLa cells (Cellonex, South Africa) as described by Okaiyeto et al (2019). The crude extracts were dissolved in dimethyl sulfoxide (DMSO) and it is noteworthy that all the solvent extracts dissolved completely in DMSO and subsequently, the crude extracts were incubated at 37 °C for 48 h at a fixed concentration of 50 µg/mL in 96-well plates containing HeLa cells.…”
Section: Cytotoxicity Assessmentmentioning
confidence: 99%